Experiences of Nursing Professionals Working With Women Diagnosed With Opioid Use Disorder and Their Newborns: Burnout and the Need for Support. (February 2021) - Reese, Sarah E.; Riquino, Michael R.; Molloy, Jen; Nguyen, Van; Smid, Marcela C.; Tenort, Bernice; Gezinski, Lindsay B.
Abstract : Background: As the rate of opioid use in pregnancy escalates, there are a growing number of women diagnosed with opioid use disorder (OUD) and their newborns being cared for in inpatient settings. Purpose: In this study, we sought to better understand the experiences of nurses and nursing assistants working with women diagnosed with OUD and their newborns. By identifying the needs of nurses and nursing assistants, the findings from this study may contribute to reductions in stigma and improved patient care. Methods: Nurses and nursing assistants were recruited from a postpartum unit at a large urban hospital in Utah. Participants (n = 30) attended up to 4 semistructured focus groups. We utilized Braun and Clarke's 6-phase approach to thematic analysis to analyze transcribed interviews. Findings/Results: Themes identified during the data analysis process included negative feelings and reactions toward patients; preferential concern for the newborn over maternal well-being; and identification of organizational and training needs to overcome these challenges. Implications for Practice: These findings identify strategies for addressing challenges faced by nurses and nursing assistants in caring for women diagnosed with OUD and their newborns. Implications for Research: Future research should examine the effectiveness of approaches to reduce behaviors influenced by stigma among nurses and nursing assistants working with women diagnosed with OUD and their newborns, as well as employee and patient satisfaction, and long-term health outcomes.